EVALUATION OF TREATMENT OUTCOMES OF CHRONIC TONSILITIS USING CO2 LASER TONSILLECTOMY AT XUYEN A VINH LONG HOSPITAL - Tran, Ngoc Nam Phuong; Châu, Chiêu Hòa (Tạp chí Tai Mũi Họng Việt Nam, 2024)
Introduction: Tonsillectomy is necessary when recurrent tonsillitis occurs frequently, aiming to prevent complications. It is an effective and cost-efficient treatment. CO2 laser tonsillectomy has been proven to provide good bleeding control, as the CO2 laser functions both as a surgical scalpel and a hemostatic tool.Objective: To evaluate the effectiveness of CO2 laser tonsillectomy in patients with chronic tonsillitis indicated for surgery.Subjects and Methods: A prospective cross-sectional descriptive study with intervention.Patients diagnosed with chronic tonsillitis who underwent laser tonsillectomy at Xuyen A Vinh Long Hospital from 2023 to 2024 were included.Results: A total of 74 patients underwent laser tonsillectomy, of which 35.1% were male and 64.9% female. The patients’ ages ranged from 5 to 59 years, with a mean age of 34.28 ± 12.73. All patients showed good postoperative outcomes. Most patients experienced blood loss of less than 5 ml, accounting for 58.1%. The average length of hospital stay was 2.88 ± 1.40 days. On average, normal eating resumed after 8.77 ± 2.04 days, and normal activities after 6.08 ± 2.37 days.Conclusion: CO2 laser tonsillectomy for chronic tonsillitis provides good treatment outcomes, regardless of hypertrophy grading. It helps reduce blood loss and shortens postoperative recovery time.